Doing business with Ukraine - Terterov, Marat (Global market briefings., 2005)
Now in its third edition, Doing Business with Ukraine is the most authoritative guide available to investment and trading opportunities, and to the structural, legal and market changes underway in the country. With a GDP growth of just over 12% year-on-year reported in 2004, Ukraine, one of the largest countries in Europe, now boasts one of the strongest GDP growth rates among all transition economies and one of the best in the world.